2(x-3) = -3x + 9 me ajudaaaaaaaaa
Soluções para a tarefa
Respondido por
0
oii, espero que te ajude! :)
Anexos:
![](https://pt-static.z-dn.net/files/d6c/cb96a585e36e9cc7948b557b7b8ab92c.jpg)
Respondido por
2
Boa noite!!!
![2(x - 3) = - 3x + 9 \\ 2x - 6 = - 3x + 9 \\ 2x + 3x = 9 + 6 \\ 5x = 15 \\ x = \frac{15}{5} \\ x = 3 2(x - 3) = - 3x + 9 \\ 2x - 6 = - 3x + 9 \\ 2x + 3x = 9 + 6 \\ 5x = 15 \\ x = \frac{15}{5} \\ x = 3](https://tex.z-dn.net/?f=2%28x+-+3%29+%3D+-+3x+%2B+9+%5C%5C+2x+-+6+%3D+-+3x+%2B+9+%5C%5C+2x+%2B+3x+%3D+9+%2B+6+%5C%5C+5x+%3D+15+%5C%5C+x+%3D+%5Cfrac%7B15%7D%7B5%7D+%5C%5C+x+%3D+3)
Espero ter ajudado! :)
Espero ter ajudado! :)
Perguntas interessantes
História,
11 meses atrás
Português,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Biologia,
1 ano atrás